Oxygen plasmas: a sharp chisel and handy trowel for nanofabrication. Issue 37 (18th September 2018) - Bazaka, K.; Baranov, O.; Cvelbar, U.; Podgornik, B.; Wang, Y.; Huang, S.; Xu, L.; Lim, J. W. M.; Levchenko, I.; Xu, S.
Abstract : Oxygen plasmas feature certain properties that make them attractive not only for material removal via etching and sputtering, but also for driving and sustaining nucleation and growth of various nanostructures in plasma bulk and on plasma-exposed surfaces. Abstract : Although extremely chemically reactive, oxygen plasmas feature certain properties that make them attractive not only for material removal via etching and sputtering, but also for driving and sustaining nucleation and growth of various nanostructures in plasma bulk and on plasma-exposed surfaces. In this minireview, a number of representative examples is used to demonstrate key mechanisms and unique capabilities of oxygen plasmas and how these can be used in present-day nano-fabrication. In addition to modification and functionalisation processes typical for oxygen plasmas, their ability to catalyse the growth of complex nanoarchitectures is emphasized. Two types of technologies based on oxygen plasmas, namely surface treatment without a change in the size and shape of surface features, as well as direct growth of oxide structures, are used to better illustrate the capabilities of oxygen plasmas as a powerful process environment. Future applications and possible challenges for the use of oxygen plasmas in nanofabrication are discussed.